Atypical Ductal Hyperplasia at the Margin of Lumpectomy Performed for Early Stage Breast Cancer: Is there Enough Evidence to Formulate Guidelines?. (4th December 2012) - Baker, Jennifer L.; Hasteh, Farnaz; Blair, Sarah L.
Abstract : Background . Negative margins are associated with a reduced risk of ipsilateral breast tumor recurrence (IBTR) in women with early stage breast cancer treated with breast conserving surgery (BCS). Not infrequently, atypical ductal hyperplasia (ADH) is reported as involving the margin of a BCS specimen, and there is no consensus among surgeons or pathologists on how to approach this diagnosis resulting in varied reexcision practices among breast surgeons. The purpose of this paper is to establish a reasonable approach to guide the treatment of ADH involving the margin after BCS for early stage breast cancer. Methods . the published literature was reviewed using the PubMed site from the US National Library of Medicine. Conclusions . ADH at the margin of a BCS specimen performed for early stage breast cancer is a controversial pathological diagnosis subject to large interobserver variability. There is not enough data evaluating this diagnosis to change current practice patterns; however, it is reasonable to consider reexcision for ADH involving a surgical margin, especially if it coexists with low grade DCIS. Further studies with longer followup and closer attention to ADH at the margin are needed to formulate treatment guidelines.